2023
DOI: 10.1186/s40104-023-00863-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of genomic prediction for meat quality traits using whole genome sequence data in pigs

Abstract: Background Pork quality can directly affect customer purchase tendency and meat quality traits have become valuable in modern pork production. However, genetic improvement has been slow due to high phenotyping costs. In this study, whole genome sequence (WGS) data was used to evaluate the prediction accuracy of genomic best linear unbiased prediction (GBLUP) for meat quality in large-scale crossbred commercial pigs. Results We produced WGS data (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Another simulation study showed that the accuracy of genomic prediction increased by up to 30% when WGS data captured causal variants with a low minor-allele frequency [12]. However, in practical applications, the use of WGS data for genomic prediction in pig populations has not shown substantial improvements in accuracy compared to traditional SNP chip data, particularly when analyzed within specific breeds [13,14]. Other studies have found a slight increase in prediction accuracy (e.g., from 0.3 to 3.5%) for some economic traits within or across pig populations, depending on the different prediction methods used [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Another simulation study showed that the accuracy of genomic prediction increased by up to 30% when WGS data captured causal variants with a low minor-allele frequency [12]. However, in practical applications, the use of WGS data for genomic prediction in pig populations has not shown substantial improvements in accuracy compared to traditional SNP chip data, particularly when analyzed within specific breeds [13,14]. Other studies have found a slight increase in prediction accuracy (e.g., from 0.3 to 3.5%) for some economic traits within or across pig populations, depending on the different prediction methods used [15,16].…”
Section: Introductionmentioning
confidence: 99%